Analysis of Food Security Strategy in Kubu Raya Regency - Nurul Fadilah; Amira Fazilah; Mentari (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to analyze food security strategies in Kubu Raya Regency, focusing on villages with limited access to food resources. The method used is a qualitative approach with a case study design. The selected villages have different food vulnerabilities, with selection criteria based on data on their high food vulnerability. The results show that food security in Kubu Raya Regency is influenced by three main dimensions: food availability, food access, and food utilization. Food availability in several villages is limited by small agricultural land areas and dependence on food distribution from outside the region. Food access is hampered by poor transportation infrastructure, while food utilization is affected by low nutritional knowledge and limited access to clean water. This study provides several strategies, including the development of agricultural and transportation infrastructure, local economic empowerment through agro-industry-based agriculture, and nutrition education to improve healthy food utilization. The proposed policy recommendations are expected to strengthen food security in Kubu Raya Regency, especially in the most vulnerable villages.